Aprovechamiento energético sostenible de un recurso geotermal: caso sala de dosificación de la Planta Luis Prieto Gómez - Ospina Betancur, Beatriz Eugenia; Murillo Arango, Walter (Ingeniería, 2022)
Context: Water treatment as an industrial process requires energy for its operation, so, in order to supply the electrical energy that requires the heating of the room in which the dosing process of chemical products is performed, the exploration of alternative energies was proposed through the determination of the environmental and financial viability of a heating system, which uses the heat of the thermal water from the Nevado del Ruiz volcano that reaches the Luis Prieto Gómez Plant. Method: A mixed type research was conducted by means of a field study to characterize the context of its use, a specialized advice to determine the heating system, and a bibliographic review to perform the financial analysis by cash flow, the environmental analysis by carbon footprint, and the sustainability of the proposal. Results: The context of the heat use was determined, and the thermal load required inside the room was characterized. Based on this characterization, it was established that a circuit system of tubular heat exchangers generated operational viability with an economic saving projection of 78 %, in comparison with a conventional system and a reduction of environmental impacts represented by a decrease of 3,25 annual tons of CO2 emitted into the atmosphere. Conclusions: The incorporation of energy sustainability for the generation of operating conditions for water treatment was achieved, starting from the conception of the use of thermal water as a renewable resource, together with the production of heat through a closed lifecycle, thus demonstrating a dialogue between the economic, environmental, and social spheres as required by sustainable development.